Global diffusion of laws: The case of minimum age of marriage legislation, 1965–2015 - Irem Ebetürk (European Journal of Cultural and Political Sociology, 2021)
The majority of countries in the world have laws setting the minimum age of marriage at 18 years old. This is a global legislative trend that intensified greatly in the 1990s. What explains this trend? To answer this question, I conduct quantitative analyses of factors influencing legislation setting the minimum age of marriage at 18. I analyse time-series data for 167 countries from 1965 to 2015 to examine which countries were early adopters of legislation. Drawing on world society theory, I theorise that global level institutionalisation of norms concerning women and children is the key to understand the passing of minimum age of marriage laws. Findings indicate that world cultural scripts and the presence of women legislators are the main impetus behind the fight against child marriage. Countries with a Muslim majority are less likely to pass laws setting the minimum age of marriage at 18.
Keywords: 300; global sociology; child marriage; human rights; globalization; world society theory